Model Integrasi Pendidikan, Kajian Keislaman, dan Pengabdian di Pondok Pesantren Nurul Cholil - Mustofa Ali; Moh Rieza Salmany; Muhammad Fahmi (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2026)
This study aimed to explore the synergy between educational activities, Islamic scholarly traditions, and community engagement implemented at Pondok Pesantren Nurul Cholil Bangkalan. The synergy was understood as an integrated pattern connecting formal and non-formal learning with the pesantren’s intellectual culture and social service practices. This research employed a descriptive qualitative approach using a case study design. Data were collected through in-depth interviews, participant observation, and document analysis. The findings indicated that the educational process at Pondok Pesantren Nurul Cholil had been carried out through a combination of the madrasiyah curriculum and progressive mastery of classical Islamic texts. Islamic scholarly activities were strengthened through regular kitab discussions, thematic study groups, and Bahtsul Masail forums that functioned as spaces for dialectical reasoning and legal analysis. Meanwhile, community engagement programs were realized through the deployment of teaching assistants, religious guidance, and social services that provided students with practical experience in applying their knowledge.These results demonstrated that the synergy of the three aspects formed a holistic and sustainable model of pesantren education that is responsive to contemporary societal needs.